PENGARUH COUNTRY OF ORIGIN DAN LABELISASI HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK MAKANAN DAN MINUMAN IMPORT DI KOTA METRO - davidson, harlley; Suwarto, Suwarto; Nasikah, Durotun (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
The large population of Indonesia makes Indonesia a market for imported products. Based on data from the Ministry of Trade, of all types of consumption goods, imports of processed food and beverages are the largest among imports of other consumer goods. Some consumer considerations in buying imported products are country of origin and the presence or absence of halal labeling. The purpose of this study was to determine the effect of country of origin and halal labeling on purchasing decisions for imported food and beverage products in Metro City. Quantitative research design. The method used is explanatory survey. The object in this study is the country of origin and halal labeling on purchasing decisions. Metro City campus educational area activities. The research population is consumers, especially students with a total sample of 100 respondents. Data collection techniques using questionnaires. The analytical tool used is data quality analysis and multiple linear regression analysis with SPSS program. The results of the study show that partial country of origin and halal labeling have a positive and significant effect on purchasing decisions. Simultaneously, country of origin and halal labeling also have a significant effect on purchasing decisions.